2021
DOI: 10.21608/edj.2021.52408.1414
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Microbiological Evaluation of the Effect of Heat Killed Lactobacillus Acidophilus and Garlic Extract on Candida Albicans in a Group of Elderly Denture Wearers

Abstract: Continuous denture wearing, lack of adequate hygiene and infection with Candida albicans (C. albicans) are among the etiological factors of Denture stomatitis (DS). The management of DS ranges from the implementation of oral hygiene measures and removal of predisposing factors to the use of antifungals, depending on the severity of inflammation. Aim of the study:This study aimed to evaluate the short-term effect of heat killed lactobacillus acidophilus -Lacteol Fort® (LF)-as a probiotic and garlic extract -Tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
(132 reference statements)
0
2
0
Order By: Relevance
“…Allicin (diallyl thiosulphonate) was assumed to be the main component among several bioactive compounds responsible for inhibiting fungal growth [ 64 ]. The enzyme alliinase converts alliin into allicin when garlic is cut or crushed [ 65 ]. Allicin is capable of transmembrane movement to combine with sulfur-containing molecular groups in proteins.…”
Section: Bioactivities Of Ge In Alleviating the Oral Pathologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Allicin (diallyl thiosulphonate) was assumed to be the main component among several bioactive compounds responsible for inhibiting fungal growth [ 64 ]. The enzyme alliinase converts alliin into allicin when garlic is cut or crushed [ 65 ]. Allicin is capable of transmembrane movement to combine with sulfur-containing molecular groups in proteins.…”
Section: Bioactivities Of Ge In Alleviating the Oral Pathologiesmentioning
confidence: 99%
“…Furthermore, the C. albicans counts were 1.89 ± 0.928 for LF, which was initially 48 ± 3.202 and 3.33 ± 1.14 for GE, which was initially 48.78 ± 2.99, while for control, it was 42 ± 4.272, which was initially 49 ± 3.87. Similarly, C. albicans biofilm-forming activity was 0.26 ± 0.07 and 0.31 ± 0.08 for LF and GE, respectively, whereas for the control, it was 5 ± 0.43 [ 65 ]. A recent in vitro study reported the essential oil of GE was more effective than fluconazole in inhibiting both planktonic cells in vitro and biofilms of different Candida species ( C. albicans , C. glabrata , C. tropicalis and C. krusei ) isolated from dental prostheses while studying the antifungal activities of essential oil of GE and fluconazole against clinical isolates of Candida species [ 71 ].…”
Section: Bioactivities Of Ge In Alleviating the Oral Pathologiesmentioning
confidence: 99%